HANGING WALL FAULT KINEMATICS AND FOOTWALL COLLAPSE IN LISTRIC GROWTH FAULT SYSTEMS - Imber J.; Childs C.; Nell P.A.R.; Walsh J.J.; Hodgetts D.; Flint S. (My University, 2003)
We describe the structure of a listric growth fault system from SE Asia, using high-resolution, 3-D seismic data. The fault system shows systematic changes in geometry and kinematics that are sympathetic with along-strike changes in the structure of the bounding fault. Where the position of the bounding fault remained fixed, there is an overall landward decrease in the age of the hanging wall growth faults. Along strike, three phases of footwall collapse caused by the active bounding fault stepping back into the footwall block were responsible for the punctuated, stepwise, landward migration of the rollover hinge and associated hanging wall growth faults during extension. The migration of these hanging wall structures is similar to that predicted by simple analogue models with fixed detachment surfaces: care should therefore be taken in defining kinematic models in areas where the geometry of the bounding fault is either poorly defined or unknown.
Keywords: GROWTH FAULT; FOOTWALL COLLAPSE; ROLLOVER; KINEMATICS